2016
DOI: 10.18632/oncotarget.10898
|View full text |Cite
|
Sign up to set email alerts
|

Blood baseline neutrophil count predicts bevacizumab efficacy in glioblastoma

Abstract: Bevacizumab is used to treat glioblastoma; however, no current biomarker predicts its efficacy. We used an exploratory cohort of patients treated with the radiochemotherapy then bevacizumab or chemotherapy at recurrence (N = 265). Bevacizumab use increased median overall survival (OS) 18.7 vs 11.3 months, p = 0.0014). In multivariate analysis, age, initial surgery, neutrophil count, Karnofsky status >70% and bevacizumab administration were independent prognostic factors of survival. We found an interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 44 publications
0
38
0
Order By: Relevance
“…In addition, Schernberg et al reported that pretreatment neutrophilia is negatively associated with overall survival in GBM patients who undergo concurrent treatment with TMZ and RT [43]. Baseline circulatory neutrophil count predicts bevacizumab efficacy in GBM patients, although the role of neutrophils in the antitumor response of anti-VEGF therapy is unclear [44]. A recent study also showed that the absolute baseline number of neutrophils is negatively associated with overall survival, and has a prognostic value for bevacizumab response in patients with recurrent GBM who have not received corticosteroids [45].…”
Section: Circulating Neutrophils In Glioma Progression and Treatment mentioning
confidence: 99%
“…In addition, Schernberg et al reported that pretreatment neutrophilia is negatively associated with overall survival in GBM patients who undergo concurrent treatment with TMZ and RT [43]. Baseline circulatory neutrophil count predicts bevacizumab efficacy in GBM patients, although the role of neutrophils in the antitumor response of anti-VEGF therapy is unclear [44]. A recent study also showed that the absolute baseline number of neutrophils is negatively associated with overall survival, and has a prognostic value for bevacizumab response in patients with recurrent GBM who have not received corticosteroids [45].…”
Section: Circulating Neutrophils In Glioma Progression and Treatment mentioning
confidence: 99%
“…Most studies to date on neutrophils and brain tumors have focused on the impact of these cells on the response to anti-angiogenic therapy and vascularity – a hallmark feature of high-grade glioma. Clinically, while it has been shown that high peripheral neutrophil count prior to treatment correlates with positive initial response to the anti-VEGF-A antibody bevacizumab (Bertaut et al, 2016), enhanced neutrophil infiltration into tumor tissue is associated with acquired resistance and higher glioma grade at later stages (Fossati et al, 1999; Liang et al, 2014) (Figure 1C). These studies and others suggest that neutrophils may have prognostic value in glioblastoma (Bertaut et al, 2016; Fossati et al, 1999; Gabrusiewicz et al, 2016; Liang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, while it has been shown that high peripheral neutrophil count prior to treatment correlates with positive initial response to the anti-VEGF-A antibody bevacizumab (Bertaut et al, 2016), enhanced neutrophil infiltration into tumor tissue is associated with acquired resistance and higher glioma grade at later stages (Fossati et al, 1999; Liang et al, 2014) (Figure 1C). These studies and others suggest that neutrophils may have prognostic value in glioblastoma (Bertaut et al, 2016; Fossati et al, 1999; Gabrusiewicz et al, 2016; Liang et al, 2014). Indeed, preclinical studies have shown that neutrophils contribute to glioblastoma progression by supporting the expansion of the glioma stem cell pool in a manner that is dependent on S100 proteins (specifically, S100A4) (Liang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 To address this possibility, researchers investigated the predictive role of the peripheral blood neutrophil count before BEV treatment on the efficacy of BEV. 36 A total of 256 GBM patients have been included in the analysis since 2006 and the best cut-off for the baseline neutrophil count was found to be 6000/mm 3…”
Section: Peripheral Neutrophil Countmentioning
confidence: 99%